1998
DOI: 10.1002/hep.510280211
|View full text |Cite
|
Sign up to set email alerts
|

Decreased survival in rat liver transplantation with extended cold preservation: Role of portal vein clamping time

Abstract: Primary liver graft dysfunction is currently related to cold ischemia-reperfusion injury, although a wide survival range has been reported using 24-hour preservation in cold University of Wisconsin (UW) solution. We hypothesized that the portal vein clamping time (PVCT) played a more important role than cold preservation injury in the postoperative outcome. Rat liver transplantation was performed using different clamping times after 24-hour cold ischemia in the UW solution. Survival rates, plasma tumor necrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 45 publications
2
44
3
Order By: Relevance
“…But in the course of cold storage, cells remained to be injured in different degrees with the extension of preservation time. In the period of liver cold storage, hepatocytes and SECs were all injured, especially the latter [18,19] . During warm ischemia hepatocytes were the most vulnerable cells whereas SECs were less sensitive [20] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But in the course of cold storage, cells remained to be injured in different degrees with the extension of preservation time. In the period of liver cold storage, hepatocytes and SECs were all injured, especially the latter [18,19] . During warm ischemia hepatocytes were the most vulnerable cells whereas SECs were less sensitive [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Male Sprague-Dawley rats weighing 200-300 g were purchased from Sino-British Sippr/BK Lab Animal Ltd. All rats were kept in animal quarters with controlled temperature (18)(19)(20)(21)(22)(23)(24)(25) and light (light on from 7 a.m. to 7 p.m.) and were fed with a standard laboratory chow and water in accordance with institutional animal care policies. Prior to the experimental procedure, the rats were fasted for 12 hours but allowed free access to water.…”
Section: Animalsmentioning
confidence: 99%
“…TNF-␣ is produced early after liver transplantation, and TNF-␣ production is increased in liver grafts failing from storage-reperfusion injury. 42,43 Anti-TNF-␣ antibodies reduce liver injury in models of warm and cold ischemia and reperfusion. 44,45 A variety of agents that suppress lipopolysaccharide-stimulated TNF-␣ formation by Kupffer cells also decrease graft failure from storage-reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…11 Indeed, in a recent study evaluating the precise time course and mechanism of SEC and hepatocyte death, it has been clearly shown that an early SEC necrosis followed by a limited and delayed hepatocyte apoptosis occurred under both viable [24-hour preservation in cold University of Wisconsin (UW) solution] and lethal conditions (42-hour preservation in cold UW solution). 12 The main pathologic difference between these 2 preservation conditions was the marked alteration of the hepatic microcirculation associated with a loss of extracellular matrix (ECM) and interruption of flow through sinusoids, leading to extensive hepatocyte necrosis.…”
mentioning
confidence: 99%